Modern solutions for ancient pathogens: direct pathogen sequencing for diagnosis of lepromatous leprosy and cerebral coenurosis - Young, B; Bush, S; Lipworth, S; George, S; Dingle, K; Sanderson, N; brankin, A; Walker, T; Sharma, S; Leong, J; Plaha, P; Hofer, M; et al. (Oxford University Press, 2022)
Microbes unculturable in vitro remain diagnostically challenging, dependent historically on clinical findings, histology, or targeted molecular detection. We applied whole-genome sequencing directly from tissue to diagnose infections with mycobacteria (leprosy) and parasites (coenurosis). Direct pathogen DNA sequencing provides flexible solutions to diagnosis of difficult pathogens in diverse contexts.